Identification of transcriptional signatures of cognitive resilience using single nucleus RNA sequencing. (20th December 2022) - Hadad, Niran; Telpoukhovskaia, Maria; Zhang, Jigang; Samuels, Michael; Robson, Paul; Philip, Vivek M.; Kaczorowski, Catherine C.
Abstract: Background: It is estimated that a third of the elderly population is not diagnosed with Alzheimer's disease (AD) due to the absence of cognitive impairment despite carrying risk variants of AD or presenting AD pathology post‐mortem. This suggests that at‐risk individuals may carry protective mechanisms that promote resilience to cognitive impairment, however the underlying molecular processes that promote resilience remain unknown. Method: To determine transcriptional changes associated with resilience, we profiled the hippocampal transcriptome at the single cell level in 7 resilient and 7 susceptible strains from the AD‐BXD mouse reference panel 1, a genetically diverse mouse model of AD that better mimics human AD. Here, we used contextual fear memory paradigm to assess short‐term memory function in AD‐BXDs carrying the 5XFAD mutation. Resilience was defined based on age‐related change in cognitive function relative to that of the entire AD‐BXD population, where strains showing no or lower than average decline were considered resilient. Result: Using single nucleus RNA‐sequencing, we profiled ∼220 K nuclei from the hippocampal formation and identified 32 cell clusters representing the major cell types in the hippocampus including glutamatergic neurons, GABAergic neurons, astrocytes, oligodendrocytes and microglia. With the exception of GABAergic neurons, transcriptional changes associated with the 5XFAD mutation were greater in susceptible AD‐BXDs. Gene expression changes associated with cognitive resilience were primarily observed in excitatory neurons, specifically in the CA1 and dentate gyrus and were enriched for ribosomal genes and nuclear encoded mitochondrial genes. In attempt to infer potential ligands that regulate resilience‐associated transcriptional changes we used a ligand‐target interaction analysis and predicted potential ligands regulating resilience programs in excitatory neurons. Conclusion: Our findings demonstrate that the rate of cognitive decline is concomitant with increased transcriptional changes associated with the 5XFAD mutation across cell types in the hippocampus. We show that molecular programs associated with resilience in excitatory neurons are enriched in protein metabolism, cellular respiration and translation, possibly indicating a response to energy demand and maintenance of cellular homeostasis. Neuner SM, Heuer SE, Huentelman MJ, O'Connell KMS, Kaczorowski CC. Harnessing Genetic Complexity to Enhance Translatability of Alzheimer's Disease Mouse Models: A Path toward Precision Medicine. Neuron. 2019.